RISK FACTORS FOR FALLS AMONG POSTMENOPAUSAL WOMEN IN HAYATABAD, PESHAWAR - Rana, Mashaal; Ali, Ikram; Rahman, Mujeeb Ur; Darain, Haider; Qureshi, Nazneen; Imtiaz, Mehwish (Annals of Allied Health Sciences, 2019)
OBJECTIVE: The objective of this study is to investigate the risk factors of falls in postmenopausal women. METHODS: The study was a cross sectional survey of 200 postmenopausal women aged 50 years and above resident in Hayatabad community, Peshawar. Participants were selected by convenient sampling from different phases of Hayatabad. Women with hormone replacement therapy, surgeries such as hysterectomy and women with disabilities were excluded. Fall risk was assessed by the Berg Balance scale and the risk factors of falls were investigated by a self-administered questionnaire. The data obtained was analyzed on SPSS version 20. RESULTS: Two hundred postmenopausal women with mean age 62.5± 2.7 participated in the study. Majority of the participants (n=175, 87.5%) were house wives while remaining 25 (12.5%) were having different jobs. The most significant predictor of high risk of fall was Diabetes (OR= 8.43, p <0.001), which suggested that diabetic women were 8.43 times more prone to fall than those without diabetes. The second significant predictor in the model was poor hearing (OR= 5.05. p <0.05) followed by incontinence (OR= 5.01, p <0.01) and fear of falling (OR= 4.41, p <0.05). The significant predictor of medium fall risk was muscle problem (OR= 3.13, p < 0.05) and high or low blood pressure (OR= 2.41. p <0.05) . CONCLUSION: This cross sectional survey identified risk factors that independently predicted a significantly increased risk of falling in postmenopausal women. The most significant predictor of high risk of fall was Diabetes followed by poor hearing, incontinence, and fear of falling. Increase in risk of fall was found to be related with increasing number of risk factors.